ASPEK SYARIAH DAN HALAL - Annisa Aulia Azzahra; Marizqa Mustika Dara; Nazla Minda Mahira; Dini Vientiany (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research discusses the concept of sharia and halal becoming increasingly important in business practices in Muslim-majority societies, especially in ensuring compliance with Islamic principles in economic activities. The aim of this research is to analyze the influence of implementing sharia and halal in business, as well as to understand company halal policies and their relevance in business feasibility studies. The method used in this research is a literature review that collects and analyzes reliable sources regarding sharia, halal and sharia business practices. Data was obtained from various references, including literature on sharia, halal, business ethics, and halal policies in companies, as well as analysis of business practices in markets that are predominantly Muslim. Implementing sharia and halal aspects in business not only increases consumer confidence, but also opens up wider market opportunities. Clear halal policies and halal SOPs help ensure products meet halal standards. Thus, the integration of sharia and halal in business strategy is a strategic step to achieve long-term growth and sustainability.